Nota prévia sobre uma Guttiferae nova da Amazônia - Berg, Maria Elisabeth Van Den (Acta Amazonica, 1975)
In this note, one new species of Guttiferae - Rheedia albuquerquei is proposed. It is placed in the section EURHEEDIA Planchon et Triana. This species is distinct from all other Rheedia by the remarkable angulate and cinereous branchlets, coriaceous blades and glabrous assimetric elipsoid fruits.